Utopian Delusions in Shirley Jackson’s The Lottery: A Psychoanalysis Approach - Maya Sekartaji (Universitas Brawijaya, 2022)
This study reveals the relationship between the plot, characterizations, point of view, and symbols-allegory in the short story The Lottery by Shirley Jackson. Through the psychoanalytic approach proposed by Carl Gustav Jung, this qualitative research also looks at the correlation between the utopian delusions that occur in the story. Based on the results of the textual analysis, it was found that the utopian delusion relation was found in three parts, including (1) the delusion of fidelity to tradition, (2) the delusion of time, and (3) the delusion of utopia. The application of psychoanalytic theory will propose a different point of view from previous studies which are still more focused only on the symbol-irony relation of tradition. In fact, the conflict, setting, actions of the characters, and symbols in the story are related to the human subconscious which requires perfection of action that results in delusions.